Factors Driving Consumers’ Attitudes towards Facebook Advertisements in an Emerging Market: A Case Study of Vietnam - Nguyen-Viet, Bang; Thi Hoang Nguyen, Yen; Hoang Le, Tin; Bao Do, Son (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: This study aims to: 1) determine the factors driving consumers’ attitudes towards Facebook advertisements in Vietnam; 2) examine the impact of genders and Generation Z attitudes towards Facebook advertisement in Vietnam. Methodology/Approach: This study employs a quantitative approach. Data were gathered from a sample of 477 Facebook users who are exposed to Facebook advertisements and resided in Ho Chi Minh City. Research findings: The findings of this study show that personalisation, entertainment, interactivity, informativeness, and credibility have positive effects on attitudes towards advertising while irritation and privacy concerns appear to be negatively related. In addition, this study also illustrates that interactivity plays a role in stimulating the ‘entertainment effect’ amongst the consumers. As expected, privacy concern is found to have a negative impact on credibility. Theoretical contribution/originality: This study expands the previous empirical works by integrating two additional variables – personalisation and privacy concerns with user and gratification theory. Policy implications: The result provides valuable input for advertisers. It offers an insight into facilitators and barriers of consumer acceptance towards Facebook advertisements; and how these aspects could shape customers’ perceptions of Facebook advertisements. Research limitation: First, the sample was constrained to Ho Chi Minh City, which may have limited the generalisability of the findings. Second, this study considered only a limited number of predictors of attitudes towards Facebook advertising. The next limitation is that this research was conducted for products and services advertised on Facebook in general and did not focus on a specific category of products or services. Keywords: Advertisement, Attitudes towards Advertisements, Emerging Market, Facebook, Facebook Advertisement JEL Classification: M3